Makna Asosiatif Lirik Lagu Dalam Album Laskar Cinta Dewa 19: Kajian Semantik Dan Pandangan Sufistik - Yulia Awalliyah; Fany Haifa Alia; Sili Muldiyanti; Fikri Hakim (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Associative meaning is the meaning that a word has that is interconnected with circumstances outside of language. Associative meaning is also related to changes in meaning due to the similarity of characteristics of a word. Language communities use associative meaning to express other concepts that are similar to the nature, condition or characteristics of the concept from which the word or lexeme originates. Associative meaning can be found in various fields of language arts, one of which is in song lyrics. Therefore, this research aims to describe the associative meaning and link with tasawwuf in the song lyrics in the album